Effects of minocycline on patients with acute anterior circulation ischaemic stroke undergoing intravenous thrombectomy (MIST-A): the study protocol for a multicentre, prospective, randomised, open-label, blinded-endpoint trial - Xiao Zhang; Li Yao; Jingjing Zhao; Hao Zhu; Bin Wang; Huiping Zhang; Wen Jiang; Dong Wei; Wen Liu; Zhongqing Sun; Weiwang Li; Xiangjun Yuan; et al. (BMJ Open)
Introduction Despite the implementation of mechanical thrombectomy, acute ischaemic stroke with large vessel occlusion (AIS-LVO) remains a significant health concern, characterised by substantial morbidity and mortality. Our trial aims to evaluate the efficacy and safety of minocycline in reducing infarct volume and improving functional outcomes in patients undergoing mechanical thrombectomy for anterior circulation AIS-LVO.Methods and analysis The MIST-A trial is a prospective, randomised, open-label, blinded-endpoint trial to be conducted across 12 medical centres. The study will enrol 180 adult patients who have experienced an anterior circulation AIS-LVO and have undergone mechanical thrombectomy. These patients will be randomly divided into two groups: one receiving minocycline in addition to standard care and the other receiving only standard care. The primary efficacy outcome is the change in infarct volume as measured by MRI, from baseline to day 5. The secondary efficacy outcomes include the incidence of intracerebral haemorrhage occurring within 24 hours and the clinical scores between the baseline and follow-up assessments. The primary outcome will be assessed using a mixed-effects model to determine the association between treatment and outcomes.Ethics and dissemination The study is approved by the Ethics Committee of Xijing Hospital (XJLL-KY20222186) and is registered at ClinicalTrials.gov (NCT05487417). This trial is estimated to end in the first quarter of 2025 and study findings are expected to be published in scientific journals that undergo peer review and also to be showcased at scientific conferences.Trial registration number NCT05487417.